Analisis Kelayakan Usaha Belimbing Wuluh Pada Bumbu Masakan Asam Sunti - Rhafi Faisal Ramadhan; Ujang Cahyadi (Jurnal Kalibrasi, 2026)
This study aims to evaluate the business feasibility of designing processed asam sunti products made from belimbing wuluh by analyzing various aspects, namely marketing, technical, financial, legal, and environmental. The research method used is a mixed methods approach, combining qualitative and quantitative approaches, adjusted to the characteristics of each aspect studied. The qualitative approach is used to gain an in-depth understanding of the business context, particularly in marketing and technical aspects such as segmentation strategy, production process, and organizational structure. This approach is descriptive and exploratory to identify potential opportunities and challenges in business development. Meanwhile, the quantitative approach is used to analyze financial feasibility through calculations of production and operational costs, cost of goods manufactured (COGM), payback period, break-even point (BEP), net present value (NPV), and internal rate of return (IRR). The results show that the COGM is IDR 19,662,991, with a profit margin of 40%, resulting in a selling price of IDR 19,663 per package. From a financial feasibility perspective, the payback period is achieved within 2 months and 24 days, and the break-even point can be reached at 130 units sold, with minimum revenue of IDR 2,584,906. Based on these findings, the asam sunti business design is considered feasible to operate, both operationally and financially.